Assessment of knowledge and practice of cardiovascular nurses regarding warfarin - Maryam Ehsani; Mansoureh Ashghali Farahani; Shima Haghani; Shiva Khaleghparast; Mahboubeh Malekmohammadi Memar (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Despite new anticoagulants' developments, warfarin is still one of the most commonly used medicines, particularly in the cardiovascular system. One of the significant challenges with warfarin is the prevalence of dangerous side effects such as bleeding and drug and food interactions, which can negatively affect patients if not adequately controlled. As health-care team members, nurses have a crucial role in prescribing this medicine and educating patients. In this regard, this study was conducted to determine the knowledge and practice of nurses working in the cardiovascular wards regarding warfarin. MATERIALS AND METHODS: In this cross-sectional, descriptive study, knowledge and practice of 239 nurses working in the cardiovascular wards of teaching hospitals affiliated to Iran University of Medical Sciences have been investigated using European Cardiovascular Nurses Knowledge questionnaire on anticoagulants and the checklist for high-risk drugs safety instructions. The sampling was performed through the stratified sampling method with proportional allocation. Data were analyzed using the SPSS software version 16 through descriptive and inferential statistics (independent t-test, one-way analysis of variance, and Pearson correlation coefficient) (Inc., Chicago, IL, USA). RESULTS: The mean scores of knowledge (18.51 ± 3.87) and practice (10.53 ± 2.12) were slightly higher than the median, and the lowest mean score was related to knowledge on drug interactions (7.62). The practice had a statistically significant relationship with knowledge (P < 0.001). Regarding demographic variables, there was a statistically significant relationship between nurses' knowledge and the education level (P = 0.009) and nurses' practice and age (P = 0.022), work experience (P = 0.032), and work experience in cardiovascular wards (P = 0.036). CONCLUSIONS: Based on the findings of this study, the knowledge of nurses working in the cardiovascular wards about warfarin was not sufficient, and their practice was of poor quality. Nurses' lack of knowledge and improper practice can jeopardize drug safety in patients and cause serious side effects such as bleeding. Proper training of nursing students and nurses about warfarin as a high-risk drug, its side effects, and drug-food interactions, and the emphasis on patient education in patients receiving this medicine can effectively reduce the incidence of side effects.